2009
DOI: 10.3168/jds.2008-1729
|View full text |Cite
|
Sign up to set email alerts
|

Real-time polymerase chain reaction-based identification of bacteria in milk samples from bovine clinical mastitis with no growth in conventional culturing

Abstract: In more than 30% of milk samples from clinical and subclinical bovine mastitis, bacteria fail to grow even after 48 h of conventional culture. The "no-growth" samples are problematic for mastitis laboratories, veterinarians, and dairy producers. This study provides the first investigation of the bacteriological etiology of such samples, using a real-time PCR-based commercial reagent kit. The assay targets the DNA of the 11 most common bacterial species or groups in mastitis and the staphylococcal blaZ gene (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
138
2
15

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(170 citation statements)
references
References 16 publications
8
138
2
15
Order By: Relevance
“…17 Several studies have suggested that polymerase chain reaction (PCR)-based assays can be applied to detect pathogens associated with mastitis and that it has several advantages, including rapid results, high sensitivity, and high throughput of milk samples. 17,18,24 Despite these obvious advantages, none of the described PCR assays to date is able to detect antibiotic resistance directly from milk samples. Thus, the ability to choose effective antibiotics for treatment or to make medical projections according to antibiotic resistance patterns, even if S. aureus infection has been confirmed at an early stage, is often hindered.…”
Section: Introductionmentioning
confidence: 99%
“…17 Several studies have suggested that polymerase chain reaction (PCR)-based assays can be applied to detect pathogens associated with mastitis and that it has several advantages, including rapid results, high sensitivity, and high throughput of milk samples. 17,18,24 Despite these obvious advantages, none of the described PCR assays to date is able to detect antibiotic resistance directly from milk samples. Thus, the ability to choose effective antibiotics for treatment or to make medical projections according to antibiotic resistance patterns, even if S. aureus infection has been confirmed at an early stage, is often hindered.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous cure, low bacterial viability, and pathogens not growing in standard culture media (Mycoplasma spp.) might explain this high proportion (Taponen et al, 2009). Freezing and thawing of the samples might have decreased the culture sensitivity of E. coli (Schukken et al, 1989) but was required to allow convenient transportation of samples by the herd veterinarians.…”
mentioning
confidence: 96%
“…However, the adoption of modern milking practices and implementation of the mastitis control programs has resulted in a considerable decline in the prevalence of these organisms in many modern dairy farms (Makovec and Ruegg, 2003). Today, the common environmental organisms include CNS, Streptococcus uberis, Streptococcus dysgalactiae, Klebsiella spp., and Escherichia coli (Taponen and Pyorala, 2009).…”
Section: Introductionmentioning
confidence: 99%